Intraspecific functional traits of an invasive alien plant, Hyptis suaveolens differ with respect to land use types - G. F. Akomolafe; W. O. Ocheola; R. Rosazlina; F. Ojija; S. Xue; B. E. Omomoh (Scientific Reports)
Abstract Hyptis suaveolens is an invasive alien plant which possesses traits that drive its impacts and interruption of ecosystem processes. In this study, the intraspecific functional traits of H. suaveolens were assessed in some invaded parts of Nasarawa State in Nigeria to test whether the functional traits (FTs) of H. suaveolens would differ with respect to the land use types at the different study sites. Invaded sites of size 100 m × 100 m were chosen at farmland, abandoned land and roadside of Lafia, Doma and Akwanga, Nasarawa State. At each site, the functional traits were determined towards the end of the growing season using ten consecutive 1.5 × 1.5 m2 quadrants positioned at 2 m intervals along a 100 m transect. Also, the diversity indices were quantified and compared across the sites at each location. Principal component analysis with the option of a varimax rotation was used to isolate axes of specialization of the plant at all the sites. The results showed that H. suaveolens utilize different functional traits as their drivers with respect to individual sites in the three locations. Leaf area, stem bark thickness, fine root diameter, specific root length, rooting depth, and plant height are drivers in Doma. Leaf area, root depth distribution, stem specific density, fine root diameter, leaf dry matter content, stem dry matter content, specific root length and plant height are the drivers in Akwanga. Fine root diameter, Leaf dry matter content, Root depth distribution, Leaf area, Specific root length and plant height are the drivers in Lafia. These traits are indicators of their highly competitive ability, low inflammability, efficient acquisition, usage of resources and resistance to physical hazard.